2007
DOI: 10.1136/bmj.39341.608519.be
|View full text |Cite
|
Sign up to set email alerts
|

Rapid tranquillisation in psychiatric emergency settings in India: pragmatic randomised controlled trial of intramuscular olanzapine versus intramuscular haloperidol plus promethazine

Abstract: Objective To compare the effect of intramuscular olanzapine with intramuscular haloperidol plus promethazine on rapid tranquillisation of agitated or violent people with mental illness. Design Pragmatic, allocation concealed, randomised controlled trial. Setting Emergency services of a general hospital psychiatry department in Vellore, south India. Participants 300 adults with agitated or violent behaviour as a result of mental illness; 150 randomised to intramuscular olanzapine and 150 randomised to intramusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
95
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 31 publications
0
95
0
4
Order By: Relevance
“…Because of the strength of evidence for efficacy in alleviating agitation in this population, aripiprazole IM (level 2),125, 126 lorazepam IM (level 2),125, 127 loxapine inhaled (Level 1)128, 129 and olanzapine IM (level 2)127, 130, 131, 132, 133 are recommended as the first‐line option. Sublingual asenapine (level 3),134 haloperidol IM (level 3),131, 135, 136 haloperidol IM + midazolam IM (level 3),131, 137 haloperidol IM + promethazine IM (level 3),131, 137, 138 risperidone ODT (level 3),136 and ziprasidone IM (level 3)131, 137, 139 are recommended as a second‐line treatment. Haloperidol per os (PO) (level 4),140, 141 loxapine IM (level 4) (clinical opinion), quetiapine PO (level 4),141 and risperidone PO (level 4)140 are included as third‐line options (Table 11).…”
Section: Acute Management Of Bipolar Maniamentioning
confidence: 99%
“…Because of the strength of evidence for efficacy in alleviating agitation in this population, aripiprazole IM (level 2),125, 126 lorazepam IM (level 2),125, 127 loxapine inhaled (Level 1)128, 129 and olanzapine IM (level 2)127, 130, 131, 132, 133 are recommended as the first‐line option. Sublingual asenapine (level 3),134 haloperidol IM (level 3),131, 135, 136 haloperidol IM + midazolam IM (level 3),131, 137 haloperidol IM + promethazine IM (level 3),131, 137, 138 risperidone ODT (level 3),136 and ziprasidone IM (level 3)131, 137, 139 are recommended as a second‐line treatment. Haloperidol per os (PO) (level 4),140, 141 loxapine IM (level 4) (clinical opinion), quetiapine PO (level 4),141 and risperidone PO (level 4)140 are included as third‐line options (Table 11).…”
Section: Acute Management Of Bipolar Maniamentioning
confidence: 99%
“…This study concluded that calming was more rapid and the incidence of motor-related side effects decreased in patients who received lorazepam in combination with haloperidol compared to haloperidol alone. A similar study involving haloperidol administered with promethazine concluded that this combination was more effective, with fewer side effects than a second-generation antipsychotic like olanzapine (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…The best evidence for adjunctive medications, studied in the TREC trials, is for promethazine in conjunction with haloperidol (28,29,35). Extrapyramidal side effects in patients receiving droperidol are usually treated in a similar manner, often with an anticholinergic medication such as diphenhydramine or promethazine (32).…”
Section: Introductionmentioning
confidence: 99%
“…22 Concerning side-effects, no significant differences were observed between the promethazine-haloperidol association and olanzapine, 21 but dystonia was more frequent in patients medicated with haloperidol alone. 22 At any rate, the available data indicate a primarily sedative effect of promethazine.…”
mentioning
confidence: 99%
“…Currently available evidence suggests that the sedative effects of the association of promethazine and haloperidol could be stronger than those obtained with the use of olanzapine 21 or haloperidol alone. 22 Concerning side-effects, no significant differences were observed between the promethazine-haloperidol association and olanzapine, 21 but dystonia was more frequent in patients medicated with haloperidol alone.…”
mentioning
confidence: 99%